On the origin and propagation of Denmark Strait overflow water anomalies in the Irminger Basin. Issue 3 (19th March 2015) - Jochumsen, Kerstin; Köllner, Manuela; Quadfasel, Detlef; Dye, Stephen; Rudels, Bert; Valdimarsson, Heðinn
Abstract Denmark Strait Overflow Water (DSOW) supplies the densest contribution to North Atlantic Deep Water and is monitored at several locations in the subpolar North Atlantic. Hydrographic (temperature and salinity) and velocity time series from three multiple‐mooring arrays at the Denmark Strait sill, at 180 km downstream (south of Dohrn Bank) and at a further 320 km downstream on the east Greenland continental slope near Tasiilaq (formerly Angmagssalik), were analyzed to quantify the variability and track anomalies in DSOW in the period 2007–2012. No long‐term trends were detected in the time series, while variability on time scales from interannual to weekly was present at all moorings. The hydrographic time series from different moorings within each mooring array showed coherent signals, while the velocity fluctuations were only weakly correlated. Lagged correlations of anomalies between the arrays revealed a propagation from the sill of Denmark Strait to the Angmagssalik array in potential temperature with an average propagation time of 13 days, while the correlations in salinity were low. Entrainment of warm and saline Atlantic Water and fresher water from the East Greenland Current (via the East Greenland Spill Jet) can explain the whole range of hydrographic changes in the DSOW measured downstream of the sill. Changes in the entrained water masses and in the mixing ratio can thus strongly influence the salinity variability of DSOW. Fresh anomalies found in downstream measurements of DSOW within the Deep Western Boundary Current can therefore not be attributed to Arctic climate variability in a straightforward way.